Effect of Dietary Cannabis sativa L. Residue Supplementation on Meat Quality and Flavor-Enhancing Free Amino Acids in Broiler Chickens - Yusup Sopian; Katatikarn Sahatsanon; Apinya Satsook; Chaiwat Arjin; Korawan Sringarm; Chompunut Lumsangkul; Panneepa Sivapirunthep; Chanporn Chaosap (My University, 2025)
This study investigated the effects of dietary Cannabis sativa residues (CR) on broiler growth and meat characteristics. A total of 256 one-day-old male Ross-308 broilers were randomly assigned to four treatments: a basal diet (control) and diets containing 0.5%, 1%, and 2% CR. CR supplementation had no effect on growth performance, survival rate, or European production index but reduced average daily feed intake (p < 0.01). No significant differences were found in meat pH, color, drip loss, thawing loss, cooking loss, or shear force (p > 0.05). However, the ΔE values (0.5% CR: 3.97, 1.0% CR: 3.71, 2.0% CR: 4.95) indicated perceptible color differences compared to the control. CR significantly reduced C12:0, C20:1n9, and C22:1n9 fatty acids (p < 0.05) while increasing free amino acids, including aspartic acid, serine, proline, methionine, and phenylalanine (p < 0.05). It also increased moisture content and decreased fat content, especially at 2% CR (p < 0.05). In conclusion, CR supplementation improves the flavor and nutritional value of broiler meat and is a potential alternative to conventional feed additives.
Keywords: Residue (chemistry); Cannabis sativa; Animal Nutrition and Physiology